Acquired Palatal Fistula in Patients with Submucous and Incomplete Cleft Palate before Surgery - Park, Ie Hyon; Chung, Jee Hyeok; Choi, Tae Hyun; Han, Jihyeon; Kim, Suk Wha (Archives of Plastic Surgery, 2016)
It is uncommon for a palatal fistula to be detected in individuals who have not undergone surgery, and only sporadic cases have been reported. It is even more difficult to find cases of acquired palatal fistula in patients with submucous or incomplete cleft palate. Herein, we present 2 rare cases of this phenomenon. Case 1 was a patient with submucous cleft palate who acquired a palatal fistula after suffering from oral candidiasis at the age of 5 months. Case 2 was a patient with incomplete cleft palate who spontaneously, without trauma or infection, presented with a palatal fistula at the age of 9 months.
Keywords: Fistula; Oral fistula; Cleft palate